Beyond landraces : framework for the genetic improvement of Bambara groundnut [Vigna subterranea (L.) Verdc.] for global food security - Bamba, Aliyu Siise Abdullah (2017)
The world over the past decades has gone through some steady bio-physical and socio-demographical changes. Specifically, climate change (leading to increased temperature, salinization, drought etc.), population explosion, urbanization and migration (especially, rural to urban migration), among others have resulted in a new set of global challenges. In this regard, the threat to global food security has been recognised as one of the key challenges facing humanity in this 21st century. The Green Revolution of the 1960s was a major success in safeguarding global food security and still remains relevant. Nonetheless, it left behind some negative footprints. Worthy of note, is the ‘erosion’ in species diversity due to the mono-culture cultivation systems it was primarily design for. For this reason, there are serious concerns that the yield gains possible with the small number of ‘major’ staple crop species [mainly cereals; wheat (Triticum spp.), rice (Oryza sativa) and maize (Zea mays) that have supported our food through the Green Revolution for the past four decades may not be enough to sustain a growing global population in the face of climate change. Recently, the accession that there is the need for policy shift on addressing global food security, away from the classical concept of the ‘Green Revolution’ is gaining some level of acceptance. Against this backdrop, exploiting underutilised crop plants with an abundance of genetic resources and potentially beneficial traits is seen as one of the solutions that could provide a more diversified agricultural system and additional food sources. For this reason, Bambara groundnut [Vigna subterranea (L.) Verdc.] has provided a focus for exemplar studies particularly in the developing world (Africa), through its ability to produce yields with minimal inputs in drought prone environments. However, typical of most underutilised species which have suffered neglect within the research community, landraces which have been selected by farmers remain the main source of planting materials. These landrace collections, in most cases may not possess the ‘optimum combinations’ of phenotypic traits desired by potential stakeholders interested in the crop (particularly; consumers, processors and farmers). The ability to develop improved germplasm resources of Bambara groundnut (through controlled breeding) is an important step towards harnessing the potentials of the crop to address food and nutritional security concerns. In this light, the need to establish a ‘coordinated breeding programmes’ for Bambara groundnut has gain some level of attention. As part of this initiative, this project reports herein; 1.Identification and critical analysis of core breeding objectives for Bambara groundnut that could be of particular importance to various stakeholders across the value chain of the crop. Additionally, a conceptual breeding framework that could serve as de facto guide for current and future breeding programmes has been reported. 2.Diversity (genetic and phenotypic) and population structure analysis of Bambara groundnut ‘global germplasm’ with emphasis on its implications for breeding programmes. Potential implications for ‘domestication theory’ have also been highlighted. Additionally, a conceptual framework of population structure of Bambara groundnut indicating its utility and linkages for crop improvement programme has been reported. 3.Heritability and response to selection (genetic advance) estimates of phenotypic traits in F2 genotypes of Bambara groundnut. 4.Development of improved germplasm resources for traits analysis in Bambara groundnut (with potential for drought studies). 5.Mapping and QTL analysis of phenotypic traits in F2 and F3 derived genotypes of Bambara groundnut.